2008
DOI: 10.1038/ajh.2008.244
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Longitudinal Systolic Dysfunction Is an Independent Marker of Cardiovascular Risk in Patients With Hypertension

Abstract: Longitudinal systolic dysfunction is an independent marker of cardiovascular risk in hypertensive patients. Despite similarity in predictive accuracy, longitudinal indices are more sensitive but less specific than circumferential indices for the prediction of cardiovascular events in these subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…A study (25) detected that the shortening of the left ventricular long-axis contributed to almost 70% of the LVEF. Studies have demonstrated that the MAD may have important clinical value in the application of the left ventricular longitudinal functions to the evaluation of early diagnosis of heart damage (26), heart disease efficacy evaluation (27), prediction of cardiovascular events (28) and prognosis of certain heart diseases (29). …”
Section: Discussionmentioning
confidence: 99%
“…A study (25) detected that the shortening of the left ventricular long-axis contributed to almost 70% of the LVEF. Studies have demonstrated that the MAD may have important clinical value in the application of the left ventricular longitudinal functions to the evaluation of early diagnosis of heart damage (26), heart disease efficacy evaluation (27), prediction of cardiovascular events (28) and prognosis of certain heart diseases (29). …”
Section: Discussionmentioning
confidence: 99%
“…This has implications for the methods which should be used to sequentially assess such patients in a clinical setting. The TDI s′ velocity has been shown to be an independent marker of CV risk in adult patients with hypertension 34 and nonischemic dilated cardiomyopathy. 35 Our analysis addressed the potential interaction of systolic and diastolic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Although several studies have focused on its utility as an early marker of LV contractile impairment, [16][17][18][19] few data are available concerning its prognostic value. While a reduced S m was found to be strongly associated with a poor outcome in systemic hypertension, 3 no independent prognostic value was reported in patients with systolic HF of a predominantly ischemic etiology. 7,8 However, it should be argued that one of these studies enrolled patients with a severely compromised LV systolic function (mean LV EF 24.7%), 7 whilst the other had a relatively short follow-up (7 months).…”
Section: Discussionmentioning
confidence: 95%
“…A relationship between longitudinal LV systolic velocity and clinical outcome has been demonstrated in different study populations. [3][4][5] However, there is still some controversy regarding the prognostic impact of TD-derived long-axis LV myocardial velocities in patients with chronic systolic HF. [6][7][8] This is likely to originate from the differences in the techniques used to measure LV myocardial velocities and, most importantly, as a result of the regional wall motion abnormalities of patients with an ischemic cardiomyopathy that might affect long-axis function.…”
mentioning
confidence: 99%